The effects of increased body mass index on preconception health - Petra Petročnik; Mirko Prosen; Ana Polona Mivšek (Nurses and Midwives Association of Slovenia, 2023)
Introduction: The growing proportion of overweight and obese people worldwide is of great concern as it affects the overall health of people and consequently also their  reproductive health. The aim of this literature review is to  examine how increased body mass index affects fertility and preconception health in men and women. Methods: A scoping literature review was conducted in February 2021 using PubMed and Medline databases, as well as the Google Scholar search engine. Inclusion criteria consisted of scientific literature, regardless of methodology, and articles published in Slovene and English. Results: The literature search yielded 9 reviews and 5 original quantitative studies published in English in the last 15 years. The results suggest that there is compelling evidence that obese individuals are at increased risk of various health problems in the pre-conception period that  may affect their fertility and ability to conceive. Discussion and conclusion: The rising prevalence of high body mass index is changing the reproductive health of men and women. Growing obesity rates, particularly in the Western world, call for greater awareness of this metabolic syndrome and its impact on female and male reproduction. Health professionals working with couples in the pre-conception period should have sufficient knowledge to address the impact of high body mass index on reproductive health and promote a healthy lifestyle.